Public schools' characteristics and teacher turnover in Oman. - Al Balushi, Ruqaiya M.; Idris, Khairuddin; Omar, Zoharah; Basri, Ramli; Kumar, Naresh (Consortia Academia Publishing, 2014)

(untitled)
Teachers are the backbone of the educational systems and their turnover may threaten the whole educational system in any country. In Oman, teacher turnover is a neglected area of study and this article may help in shedding some light on teacher turnover phenomenon in Oman. The purpose of this study is to investigate the influence of school characteristics (e.g., school size, gender, time-shift, education type, and school location) on the turnover intentions of teachers in public schools in Oman. Survey questionnaires were used to collect data from 214 public schools in Oman. 142 schools from all educational regions in Oman were participated in this study. Data analyses tools for this study were descriptive statistics such as mean and standard deviation, in addition to independents t-test and analysis of variance. The study revealed that teacher intentions to transfer to other schools are influenced by almost all the studied school characteristics. Policy makers and human resource recruiters in Ministry of Education should be aware of teachers’ preferences for certain schools to avoid teachers’ shortage in non-preferred schools. Further studies about the influence of school time-shift and teachers’ intentions to quit or transfer are needed to affirm the results in this study. This is the first study about the influence of school characteristics on teacher turnover in public schools in Oman. Thus, the value of this study stems from the uniqueness of this study which may serve as an eye opening indicator about teacher turnover in Oman.